MEMBERDAYAKAN KEMAMPUAN BERPIKIR MAHASISWA MELALUI MODEL PEMBELAJARAN READING QUESTIONING AND ANSWERING (RQA) - Mulyadi Mulyadi; Adlim Adlim; Djufri Djufri (Biotik, 2014)
This study aimed at figuring out the increase of student thinking skills through the preparation of questions. The population of the research was all of four-semester students of Biology Department of Teacher Training and Education (Tarbiyah) Faculty of IAIN Ar-Raniry in academic year 2012/2013. The sample then selected 29 students. The method used was experimental research. The researcher taught by using Questioning Reading and Answering learning model. Students are asked to read the course topic and then prepare substantial questions from the reading. The assigned materials were Bryophyta and Pteridophyta. The test of thinking skill followed the rubric of knowledge dimensions and cognitive process dimensions of Anderson and Karthwohl. The results showed an increase in thinking ability of students toward the higher level thinking ability. Thus the application of the Reading Questioning and Answering model can improve thinking ability of students in Botany Cryptogamae course.